Pengaruh Motivasi Dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Direktorat Industri Elektronika Dan Telematika Kementrian Perindustrian - Hansfriyadi, Syammas; Krisyanto, Edy (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Abstrak. This study aims to determine the influence of motivation and organizational culture on employee performance partially and simultaneously at Direktorat Industri Elektronika dan Telematika, Kementerian Perindustrian. The research method used is quantitative with a survey approach, and the data analysis method uses linear regression, correlation, determination, t-test, F-test. The results of the study indicate that: (1) There is a significant influence between Motivation (X1) partially on Employee Performance (Y) at the Directorate of Electronics and Telematics Industry, Ministry of Industry, as evidenced by the calculated t value of 5.505 > t table 2.028 or Sig value of 0.000 < 0.05, simple linear regression equation Y = 14.698 + 0.610 X1, correlation value rx1.y 0.676 and the contribution of the influence of the motivation variable (x1) on performance (y) of 45.7% and the remaining 54.3% is influenced by other factors. (2) There is a significant influence between Motivation (X1) and Organizational Culture (X2) simultaneously on Employee Performance (Y) at the Directorate of Electronics and Telematics Industry, Ministry of Industry, as evidenced by the calculated t value of 4.891 > t table 2.028 or a Sig value of 0.000 < 0.05, a simple linear regression equation of Y = 15.468 + 0.590 X2, a correlation value of rx2.y of 0.632 and the contribution of the influence of the organizational culture variable (x2) on performance (y) of 39.9% and the remaining 60.1% is influenced by other factors. (3) There is a significant influence between Motivation (X1) and Organizational Culture (X2) simultaneously on Employee Performance (Y) at the Directorate of Electronics and Telematics Industry. Ministry of Industry, proven by the calculated F value of 18.743 > F table 3.267 or a Sig value of 0.000 < 0.05, the multiple linear regression equation Y = 10.414 + 0.414 X1 + 0.306 X2, the correlation value rx12.y 0.719 and the contribution of the influence of the motivation variable (x1) and organizational culture (x2) on performance (y) of 49% and the remaining 51% is influenced by other factors